A Review of Heat Flow Control and Enhancement Techniques - Shailesh Singh Thakur, (AG Volumes, 2022)
Most nanoelectronic systems have serious problems with heat dissipation and thermal management, which are important hurdles in many scientific and technological fields. Experimental improvements in thermal characterisation and phonon engineering have greatly improved our knowledge of heat transport and shown us effective techniques to regulate its propagation in nanomaterials; these are the topics we discuss in this review. We provide a comprehensive overview of the most recent phonon engineering techniques for 2D materials and semiconductor nanostructures, such as graphene and transition metal dichalcogenides, and their potential device applications. Then, we explore the fundamental difficulties and limits of thermal characterization approaches while reviewing the most recent developments in this field.